Impact Assessment of Tourism Events in Kutai Kartanegara District - Muhammad Tommy Fimi Putera; Adietya Arie Hetami; Tulus Sutopo; Fareis Althalets; Annisa Wahyuni Arsyad; Muhammad Subahan Nur (Poltanesa, 2026)
This research evaluates the impact of tourism events in Kutai Kartanegara Regency, focusing on economic, social, cultural and environmental aspects. The research aimed to identify contributions to local development and challenges in event management. A mixed methods approach was used, combining surveys, interviews, and SWOT analysis in three sub-districts: Tenggarong, Tenggarong Seberang, and Anggana. Results showed significant economic benefits, including increased local income and job creation, with 1.53 million tourists by 2023. Socially, events foster cultural pride and community interaction, although issues such as traffic congestion still exist. Environmentally, post-event waste management is effective, but infrastructure is still temporary. The SWOT analysis highlights strengths in cultural heritage and government support, but weaknesses include limited promotion and infrastructure. Opportunities lie in event expansion, while threats include funding dependency. Recommendations include increased digital promotion, infrastructure improvements, and public-private collaboration for sustainable tourism development.